Тонкоголкова аспіраційна пункційна біопсія вузлів щитоподібної залози: показання, техніка, клінічне застосування - Хоперія, В. Г. (Clinical Endocrinology and Endocrine Surgery, 2011)
FNA thyroid nodules is a highly sensitive method for diagnosis of nodular goiter. This method allows us not only to establish the diagnosis of thyroid tumors, but also to define the scope of the planned surgery. Increased efficiency results FNA depends on the qualifications of professionals who conduct it. The use of additional diagnostic methods such as immunocytochemistry and PCR can enhance the effectiveness of cytological diagnosis of suspicious findings. In clinical recommendations for diagnosis and treatment of thyroid nodules must include the results of FNA, clinical and epidemiological studies.